2019
DOI: 10.2147/dddt.s219533
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dexmedetomidine protects H9c2 cardiomyocytes against oxygen-glucose deprivation/reoxygenation-induced intracellular calcium overload and apoptosis through regulating FKBP12.6/RyR2 signaling</p>

Abstract: Purpose Intracellular calcium ([Ca 2+ ]i) overload is a major cause of cell injury during myocardial ischemia/reperfusion (I/R). Dexmedetomidine (DEX) has been shown to exert anti-inflammatory and organ protective effects. This study aimed to investigate whether pretreatment with DEX could protect H9c2 cardiomyocytes against oxygen-glucose deprivation/reoxygenation (OGD/R) injury through regulating the Ca 2+ signaling. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 55 publications
2
27
1
Order By: Relevance
“…In regard to the mechanism at the cellular level, several studies have confirmed the cardioprotective effect of DEX in I/R injury based on H/R models. 23,24,41 The consistent conclusions advanced from these studies share similar outcomes with our conclusions, although the H/R models used varied among the studies. The major outcomes evaluated were cell viability, the apoptosis rate and LDH release, and by evaluating the expression of miR-208b, 23 intracellular calcium overload 24 and TLR4, 41 no ERS was found to be involved.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In regard to the mechanism at the cellular level, several studies have confirmed the cardioprotective effect of DEX in I/R injury based on H/R models. 23,24,41 The consistent conclusions advanced from these studies share similar outcomes with our conclusions, although the H/R models used varied among the studies. The major outcomes evaluated were cell viability, the apoptosis rate and LDH release, and by evaluating the expression of miR-208b, 23 intracellular calcium overload 24 and TLR4, 41 no ERS was found to be involved.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, researchers have focused on studying other non-cardiac cells, such as endothelial cells, under IRI or H/R conditions 16,17 and examining several crucial ERS chaperones, proteins and apoptosis indicators produced by organs other than the heart under IRI or H/R conditions, 6,[18][19][20][21][22] finding that DEX can effectively regulate the function of non-cardiac cells and interfere in the endoplasmic reticulum stress signalling pathway under certain circumstances. Few studies have explored the function of DEX in H9c2 cardiomyocytes under H/R conditions; 23,24 however, the exact regulatory effect of DEX on ERS remains unknown. In recent years, an increasing number of basic research studies have focused on the p38MAPK signalling pathway; p38MAPK belongs to the family of MAPK-activated protein kinases and participates in many cellular processes, such as cell proliferation, survival and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…All of the above plasmids were supplied by Shanghai Gene-Pharma Co., Ltd. (Shanghai, China). The dosages used for mimic NC and miR-214 mimic were 50 nM 20,21 , and 20 nM was used for pcDNA3.1, pcDNA3.1-Kcnk2, sh-NC and sh-Foxd3 22 . After 24 h of transfection, the cells underwent hypoxia (2 h) and reoxygenation (22 h) and were the collected for subsequent experiments.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Recent studies showed that pharmacological inhibition of inflammation and apoptosis alleviated I/R-induced myocardial injury in rats or hypoxia/ reoxygenation-induced injury in cardiomyocytes (J. Chen et al, 2019;Peng et al, 2020;Yuan et al, 2019;J. J. Zhang, Peng, Zhang, Meng, & Ji, 2017).…”
Section: Introductionmentioning
confidence: 99%